2014
DOI: 10.1136/annrheumdis-2014-205227
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the development of clinical arthritis in anti-CCP positive individuals with non-specific musculoskeletal symptoms: a prospective observational cohort study

Abstract: NCT02012764 at ClinicalTrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
191
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(200 citation statements)
references
References 40 publications
5
191
1
3
Order By: Relevance
“…There are no data given for the comparison of the 24-month results in the van de Stadt (2013) cohort [3]. Rakieh et al (2015) investigated a similar cohort of one hundred seropositive arthralgia patients [15] and found comparable results to van de Stadt et al (2013) (3). After an observation period of 12 months 34% of the patients had developed RA and after 24 months 44%.…”
Section: Incidence Of Ra Manifestationmentioning
confidence: 64%
See 2 more Smart Citations
“…There are no data given for the comparison of the 24-month results in the van de Stadt (2013) cohort [3]. Rakieh et al (2015) investigated a similar cohort of one hundred seropositive arthralgia patients [15] and found comparable results to van de Stadt et al (2013) (3). After an observation period of 12 months 34% of the patients had developed RA and after 24 months 44%.…”
Section: Incidence Of Ra Manifestationmentioning
confidence: 64%
“…There is data investigating the course of disease in ACPA-positive arthralgia patients qualifying for a comparison of these results [13,15,3].…”
Section: Incidence Of Ra Manifestationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in those with genetic risk factors, the additional presence of RA-related autoantibodies appears to add significant predictive power; in a recent prospective study of healthy relatives of RA patients, anti-CCP positivity was associated with a 5-year PPV of 61%, compared to 0.4% in anti-CCPnegative subjects (47). Likewise, seropositive individuals with joint symptoms appear to have a markedly higher risk of arthritis development (48)(49)(50), with absolute risks of up to 50% at 12 months. These studies are not directly comparable, but the striking gains in predictive ability highlight the value of combining autoantibodies with other variables in order to achieve clinically useful risk stratification.…”
Section: Gutmentioning
confidence: 99%
“…It is therefore useful to know if a particular symptom complex can identify those at higher risk of progression to arthritis, over and above laboratory biomarkers such as serology. Evidence from Dutch and UK cohorts indicates that symptoms add significant predictive power in seropositive individuals (48)(49)(50). Bos et al found that 20% of their cohort of ACPA and/ or RF-positive patients with arthralgia of any form experienced progression to arthritis after a median follow-up of 28 months (48).…”
Section: Clinical Features: How Do At-risk Individuals Present?mentioning
confidence: 99%